Bacterial cellulose/triethanolamine based ion-conducting membranes - De Salvi, Denise T. B. [UNESP]; Barud, Hernane S. [UNESP]; Pawlicka, Agnieszka; Mattos, Ritamara I.; Raphael, Ellen; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP] (Springer, 2014)
New bacterial cellulose (BC)-triethanolamine (TEA) ion-conducting membranes have been prepared and characterized. The samples were obtained by soaking BC membranes in triethanolamine aqueous solutions and drying. The scanning electron microscopy pictures revealed that the incorporation of TEA in BC membranes covers the cellulose microfibrils. Raman spectra exhibited BC and TEA characteristic group frequencies and thermal analysis evidenced an influence of TEA content on the sample thermal stability. The ion-conductivity as a function of the temperature showed an Arrhenius behavior increasing from 1.8 x 10(-5) S/cm at room temperature to 7.0 x 10(-4) S/cm at 80 A degrees C for the BC-TEA 1 M sample.
Keywords: Bacterial cellulose; Ion-conduction; Triethanolamine; Membranes